Burden of influenza in Latin America and the Caribbean: a systematic review and meta‐analysis. Issue 6 (5th December 2012) - Savy, Vilma; Ciapponi, Agustín; Bardach, Ariel; Glujovsky, Demián; Aruj, Patricia; Mazzoni, Agustina; Gibbons, Luz; Ortega‐Barría, Eduardo; Colindres, Rómulo E.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Savy et al. (2012) Burden of influenza in Latin America and the Caribbean: a systematic review and meta‐analysis. Influenza and Other Respiratory Viruses DOI: 10.1111/irv.12036. Objective Influenza causes severe morbidity and mortality. This systematic review aimed to assess the incidence, etiology, and resource usage for influenza in Latin America and the Caribbean. Design Meta‐analytic systematic review. Arcsine transformations and DerSimonian Laird random effects model were used for meta‐analyses. Setting A literature search from 1980 to 2008 in MEDLINE, Cochrane Library, EMBASE, LILACS, Ministries of Health, PAHO, proceedings, reference lists, and consulting experts. Sample We identified 1092 references, of which 31 were finally included, in addition to influenza surveillance reports. We also used information from the 10 reports from the collaborative group for epidemiological surveillance of influenza and other respiratory virus (GROG), and information retrieved from the WHO global flu database FLUNET. Main outcome measures Incidence, percentage of influenza specimens out of the total received by influenza centers and resource‐use outcomes. Results A total of 483 130 specimens of patients with influenza were analyzed. Meta‐analysis showed an annual rate of 36 080 (95%CI 28 550 43 610) influenza‐like illness per 100 000 persons‐years. The percentage of influenza out of total specimens received by influenza centers ranged between 4.66% and 15.42%, with type A the most prevalent, and A subtype H3 predominating. The mean length of stay at hospital due to influenza ranged between 5.8 12.9 days, total workdays lost due to influenza‐like illnesses were 17 150 days, and the mean direct cost of hospitalization was US$575 per laboratory‐confirmed influenza case. Conclusions Our data show that seasonal influenza imposes a high morbidity and economic burden to the region. However, the vaccine‐uptake rate has been low in this region. Population‐based cohort studies are required to improve the knowledge about incidence and resource utilization, which would inform healthcare authorities for decision making.